Comparison of remineralization in caries-affected dentin using calcium silicate, glass ionomer cement, and resin-modified glass ionomer cement: an in vitro study - Kwanchanok Youcharoen; Onwara Akkaratham; Papichaya Intajak; Pipop Saikaew; Sirichan Chiaraputt (Restorative Dentistry & Endodontics, 2025)
Objectives: This study evaluated the ability of calcium silicate cement (CSC) as a remineralizing agent compared with conventional glass ionomer cement (GIC) and resin-modified GIC (RMGIC) to remineralize artificial caries-affected dentin. Methods: Twenty-five class V cavities were prepared on extracted human third molars. Twenty teeth underwent artificial caries induction. The remaining five teeth with sound dentin serve as the positive control. The twenty demineralized teeth were subdivided into four groups (n = 5): carious dentin without restoration (negative control [NC]), carious dentin restored with CSC (Biodentine, Septodont), carious dentin restored with GI (Fuji IX, GC Corporation), and carious dentin restored with RMGIC (Fuji II LC, GC Corporation). Following restoration, the specimens were stored in artificial saliva for 7 days. The elastic modulus was evaluated by a nanoindentation test. The mineral composition was analyzed by scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDX), and the mineral composition at the dentin-material interface. Results: CSC had a higher modulus of elasticity compared to GI, RMGI, and NC groups (p < 0.05). Higher calcium and phosphorus content was observed under CSC restorations, as indicated by SEM-EDX examination, which may lead to better remineralization. Conclusions: Compared to GI and RMGI, CSC showed the best remineralization and mechanical reinforcement in caries-affected dentin, indicating CSC for use in minimally invasive restorative dentistry.
Keywords: Dental materials and restorations; Endodontics and Root Canal Treatments; Dental Health and Care Utilization